2010
DOI: 10.1038/onc.2010.315
|View full text |Cite
|
Sign up to set email alerts
|

AP1 factor inactivation in the suprabasal epidermis causes increased epidermal hyperproliferation and hyperkeratosis but reduced carcinogen-dependent tumor formation

Abstract: AP1 (jun/fos) factors comprise a family of transcriptional regulators (c-jun, junB, junD, c-fos, FosB, Fra-1 and Fra-2) that are key controllers of epidermal keratinocyte survival and differentiation, and are important drivers of cancer development. Understanding the role of these factors in epidermis is complicated by the fact that each member is expressed in defined cell layers during epidermal differentiation, and because AP1 factors regulate competing processes (i.e., proliferation, apoptosis and different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
68
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(71 citation statements)
references
References 57 publications
3
68
0
Order By: Relevance
“…The transcription factors include AP1, CCAAT enhancer-binding protein, and Sp1, which move to the nucleus and bind to specific sites on the involucrin promoter to activate expression (48,(67)(68)(69)(70)(71). This molecular mechanism has been confirmed using transgenic mouse models (72)(73)(74)(75)(76).…”
Section: Discussionmentioning
confidence: 69%
“…The transcription factors include AP1, CCAAT enhancer-binding protein, and Sp1, which move to the nucleus and bind to specific sites on the involucrin promoter to activate expression (48,(67)(68)(69)(70)(71). This molecular mechanism has been confirmed using transgenic mouse models (72)(73)(74)(75)(76).…”
Section: Discussionmentioning
confidence: 69%
“…In the course of studies designed to understand AP1 transcription factor function in epidermis, we produced mice in which AP1 transcription factor function is inactivated in the suprabasal epidermis (Rorke et al , 2010). In this model, we induce suprabasal epidermal expression of TAM67, a dominant-negative form of c-jun which inhibits AP1 factor function, using a doxycycline-inducible system.…”
Section: Discussionmentioning
confidence: 99%
“…1C). C-Jun is the most extensively studied protein of AP-1 components and has also been reported to be involved in the regulation of numerous cell activities, such as proliferation, survival, tumorigenesis and apoptosis (2425). The transcriptional activation of c-Jun depends on its phosphorylation at Ser 63 and 73 in the transactivation domain (89, 11).…”
Section: Resultsmentioning
confidence: 99%
“…Our previous studies have strongly indicated that Chel A treatment leads to p53 protein accumulation and activation by preventing p53 proteins from degradation (4). c-Jun is a key member of the activator protein-1 (AP-1) family of transcription factors which bind to AP-1 elements in their target genes (37), and c-Jun/AP-1 activation is involved in the regulation of numerous cell biological activities, such as proliferation, survival, tumorigenesis and apoptosis (2425). c-Jun appears to be both a positive and a negative regulator of apoptosis (37).…”
Section: Discussionmentioning
confidence: 99%